Task Based Instruction in Teaching Speaking Skill in EFL Classroom - Safitri, Wahyuni (VELES Voices of English Language Education Society, 2018)
The aim of the study was to examine the effectiveness of task based instruction approach in teaching speaking skills of EFL learners. This research was a pre-experimental. It was conducted at the seventh grade of MTs Darul Aitam Jerowaru in the school year 2017-2018. The sample consisted of 25 students selected by using cluster random sampling technique. The data was collected using a speaking test. In analyzing the data, the researcher using paired sample t-test. The mean score of post-test (57.12) was higher than pre-test (34.56). The result of the paired sample t-test indicated that there was a significant difference in the mean scores between pre-test and post-test, t(df=24)= 49.59 at p< .01. Based on the finding, it can be concluded that task based instruction was significantly effective in teaching speaking skills.